Comparison of effective optical zone after small‐incision lenticule extraction and femtosecond laser–assisted laser in situ keratomileusis for myopia. Issue 10 (October 2018) - Hou, Jie; Wang, Yan; Lei, Yulin; Zheng, Xiuyun
Abstract : Purpose : To compare the effective optical zone (EOZ) after small‐incision lenticule extraction (SMILE) and femtosecond laser–assisted laser in situ keratomileusis (FS‐LASIK). Setting : Jinan Mingshui Eye Hospital, Jinan, China. Design : Retrospective case series. Methods : Myopic patients who had small‐incision lenticule extraction or FS‐LASIK were enrolled in this retrospective study. Effective OZs were measured at 1 week, 1 month, and 3 months postoperatively, using the tangential curvature difference map of the Scheimpflug tomography system. Correlations between the changes in the EOZ and relevant parameters were analyzed 3 months postoperatively. Results : The study comprised 76 patients (76 eyes). The mean EOZs at 1 week, 1 month, and 3 months postoperatively were 5.39 ± 0.27 mm, 5.33 ± 0.30 mm, and 5.34 ± 0.23 mm in the small‐incision lenticule extraction group and 5.06 ± 0.36 mm, 4.98 ± 0.39 mm, and 5.01 ± 0.31 mm in the FS‐LASIK group, when the programmed OZ was 6.5 mm. The magnitude of decreases in EOZ was significantly smaller in the small‐incision lenticule extraction group than in the FS‐LASIK group at all timepoints after surgery ( P < .01). There were significant correlations between changes in EOZ and corneal asphericity ( P < .01). Epithelial thickening was positively correlated with EOZ reduction in the small‐incision lenticule extraction group ( r = 0.479, P < .01); however, no correlation was found between epithelial thickening and EOZ reduction in the FS‐LASIK group ( r = .324, P > .05). Conclusions : Both small‐incision lenticule extraction and FS‐LASIK resulted in EOZ reduction during correction of myopia. However, small‐incision lenticule extraction resulted in less reduction than FS‐LASIK and was associated with corneal asphericity changes and epithelial thickening.